Type 2 diabetes mellitus and inflammation: Prospects for biomarkers of risk and nutritional intervention - Badawi A (Dove Medical Press, 2010)
Alaa Badawi1, Amira Klip2, Pierre Haddad3, David EC Cole4, Bibiana Garcia Bailo1,5, Ahmed El-Sohemy5, Mohamed Karmali11Office for Biotechnology, Genomics and Population Health, Public Health Agency of Canada, Toronto, ON, Canada; 2Cell Biology Program, The Hospital for Sick Children, Toronto, ON, Canada; 3Natural Health Products and Metabolic Diseases Laboratory, Department of Pharmacology and Montreal Diabetes Research Centre, Montreal, QC, Canada; 4Department of Laboratory Medicine and Pathobiology, 5Department of Nutritional Sciences, University of Toronto, Toronto, ON, CanadaAbstract: Obesity is a major risk factor for type 2 diabetes mellitus (T2DM), which is a significant health problem worldwide. Active disease is associated with low-grade chronic inflammation resulting in part from the activation of the innate immune system. In obesity, this activation leads to the release of pro-inflammatory cytokines such as tumor necrosis factor-α, interleukin-1β and interleukin-6 that block major anabolic cascades downstream of insulin signaling and thus disrupt insulin homeostasis and action. Cytokines also trigger the production of acute-phase reactants such as C-reactive protein, plasminogen activator inhibitor-1, serum amyloid-A, and haptoglobin. The elevated synthesis of pro-inflammatory cytokines and acute-phase proteins (inflammatory network) characterizes the early (or pre-clinical) stages of T2DM and exhibits a graded increase with the disease progression. Current evidence suggests that understanding inflammatory networks can point to new biomarkers that may permit capturing the interaction between genetic and environmental risk factors in the pathogenesis of T2DM. Such biomarkers have a significant public health potential in the prediction of disease occurrence beyond risk factors presently monitored, such as family history, lifestyle assessment and standard clinical chemistry profiles. Furthermore, inflammatory markers may assist in the evaluation of novel strategies for prevention, particularly in relation to micronutrients. This review discusses the current knowledge linking T2DM risk to inflammatory signaling pathways interacting with the innate immunity system and the prospect of inflammatory markers serving as molecular targets for prevention and/or biomarkers for early risk prediction of T2DM. The potential of micronutrients replenishment to improve insulin action by attenuating inflammation is also evaluated in the context of the public health relevance of this approach.Keywords: inflammation, biomarkers, prevention, type 2 diabetes